2014
DOI: 10.1159/000369913
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Maintenance for 2 Years after a 6-Month Randomised Controlled Trial Comparing Education-Only and Group-Based Support in Japanese Adults

Abstract: Objective: Our previous study, a 6-month randomised controlled trial, demonstrated that a group-based support promoted weight loss as compared to an education-only intervention. The purpose of this study was to examine weight loss maintenance for 2 years. Methods: Originally, 188 overweight Japanese adults, aged 40-65 years, were randomly assigned to 3 groups: control, education-only or group-based support. After the 6-month intervention, 125 participants in the education-only and the group-based support group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
5
15
1
Order By: Relevance
“…WLM accumulated the most steps per day and spent the most time stepping, followed by NC, and then OC, suggesting that achieving a high number of steps per day may play an important role in the prevention of weight gain and weight regain after weight loss. Our results are consistent with those of Nakata et al (35), who found that individuals in the highest quartile of weight loss 2 years after a 6-month intervention significantly increased their step count (by 2,607 steps/d) when compared with the lowest quartile of weight loss. In addition, WLM and NC spent 1.2 times the minutes per day standing that OC spent, suggesting that increasing time spent standing may help individuals to maintain a normal body weight.…”
Section: Discussionsupporting
confidence: 93%
“…WLM accumulated the most steps per day and spent the most time stepping, followed by NC, and then OC, suggesting that achieving a high number of steps per day may play an important role in the prevention of weight gain and weight regain after weight loss. Our results are consistent with those of Nakata et al (35), who found that individuals in the highest quartile of weight loss 2 years after a 6-month intervention significantly increased their step count (by 2,607 steps/d) when compared with the lowest quartile of weight loss. In addition, WLM and NC spent 1.2 times the minutes per day standing that OC spent, suggesting that increasing time spent standing may help individuals to maintain a normal body weight.…”
Section: Discussionsupporting
confidence: 93%
“…That program involved a more intensive intervention that was 3 months longer than our weight reduction program. Although our follow‐up duration was shorter at only 1 year, our simple and shorter program was able to produce similar weight reduction effects as those reported by Nakata et al Moreover, our worksite‐based program was designed to be more practical and economical as it was conducted during working hours.…”
Section: Discussionsupporting
confidence: 65%
“…Only one study has previously examined weight maintenance in Japanese subjects after a weight reduction program . Nakata et al compared the 2‐year weight maintenance outcomes after a 6‐month hospital‐based randomized controlled trial between Japanese adults who received an education‐only intervention and those who received group‐based support .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous randomized controlled trial (RCT) [7,8], we tested the effects of providing educational materials such as textbooks and diaries and group-based support with a 2-h single motivational lecture for the control group. Weight loss at 6 months in the control group, educational group, and group-based support group was 2.9, 4.7, and 7.7 kg, respectively.…”
Section: Introductionmentioning
confidence: 99%